KARDIOCHIRURGIA DOROSŁYCHRisk factors predisposing to deep sternal wound infection - Porubcinova, Ingrid; Porubcin, Stefan; Sabol, Frantisek; Jarcuska, Pavol (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction: Despite advances in surgical procedures, there is an increasing trend of infectious complications with substantial morbidity, prolonged length of hospitalization (LOS), readmissions and growing financial expenses. The knowledge of predisposing risk factors with regard to causative pathogens may decrease the incidence of infections. Materials and methods: The aim of our study was to determine risk factors for deep sternal wound infections (DSWI), and their stratification according to microbiological cultures in 4484 patients undergoing cardiac surgery at the Department of Cardiac Surgery, Kosice, Slovakia during 2007-2010. Results : We observed 97 (2.2%) DSWI. Incidence of DSWI increased from 0.9% to 3.1%. G+, G– and polymicrobial flora were recovered in 47.1%, 32.2% and 20.7% of patients, respectively. Significant risk factors were: obesity (BMI > 30), LOS before surgery > 2 days, LOS at ICU > 3 days, extracorporeal circulation (ECC) > 120 minutes, discharge to another medical facility, reperfusion syndrome, early surgical re-exploration, dialysis, diabetes mellitus and new-onset atrial fibrillation. We have identified the patient risk profile for DSWI caused by specific pathogens. Risk factors for G+ DSWI were BMI < 30 (p = 0.048) and peripheral atherosclerotic arterial disease (p < 0.05). The risk of G– infection was observed in women, patients older than 65 years (p = 0.01), after emergent operations (p 48 hours (p 120 minutes, longer (> 6 days) postoperative stay (p = 0.01) and in patients readmitted from another hospital (p = 0.047). Conclusion : Our study suggests that considering the patient risk profile in patients with DSWI can improve optimization of empirical antimicrobial therapy.